Botany, Ethnomedicine, Phytochemistry and Pharmacology of Musk Cucumber (Sicana odorifera) - A Review - Haleema Sadia,; Malik, Khafsa; Naqvi, Syed Azaz Mustafa; Hassan, Ahmad; Abbas, Sibtain (Ethnobotany Research and Applications, 2024)
Background: Sicana odorifera is a fruit with a strong aroma that is native to Brazil and is extensively dispersed throughout Tropical America, because they have historically been used to treat a variety of illnesses like diabetes, high blood pressure, inflammation, itchiness, and more, have a name as "cassabanana", "sikana", or "musk cucumber". Methods: Google Scholar, Web of Science, Sci-finder, PubMed, Elsevier, Wiley, China National Knowledge Infrastructure, Open Access Library, and SpringerLink were used to locate references about Sicana odorifera between 1963 and 2022. "The Plant List" (www.theplantlist.org) and "The World Flora Online" (www.worldfloraonline.org) gave the scientific plant names. Results: Despite being regarded as Indigenous fruits, Sicana odorifera is significant for the creation of prospective sources of herbal remedies since the community consumes them. Catechins, depsidia and depsidones, coumarins, steroids and triterpenoids, flavonoids, glycosides, along with polysaccharides, saponins, tannins, and alkaloids have all been identified using phytochemistry screening. Recent studies have shown the pharmacological effects of Sicana odorifera, including its hypoglycemic, anti-depressants, and numerous traditional uses. Even though ethnomedical uses were an invaluable resource for pharmacology, several claims that certain plants might heal conditions like anemia, the symptoms of fever, diarrhea, or discomfort in the stomach fail to be validated by recent studies. Conclusions: It is necessary to clarify the differences between ethnomedical applications and modern pharmacology and between phytochemistry screening and structural elucidation. This review shows that Sicana odorifera can be regarded as a promising source of phytomedicines whenever we look into their possible function. Keywords: Sicana odorifera, Ethnomedicine, Phytochemistry, Pharmacology.